1995
DOI: 10.1002/pssa.2211520202
|View full text |Cite
|
Sign up to set email alerts
|

Unusual behaviour of lithium tetraborate Li2B4O7 at low temperatures: An X-ray diffraction study

Abstract: Precision measurements of the lattice parameters as well as of the intensities of Bragg reflections in the temperature range from 80 to 400 K are performed. A peculiar series of anomalies are revealed: the value of the lattice parameter jumps and the intensity of the Bragg reflections depend on the number of thermal cycles. An incommensurate superstructure with wave vector of modulation q = †c* († = 0.035 at 300 K) and broad temperature range of existence (80 K > Tcom < Tinc > 400 K) is discovered in the Li2B4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…The first peaks are observed at 0.143 nm and ranged from 0.12 to 0.18 nm. Crystalline structures such as Li 2 B 4 O 7 , Li 3 B 7 O 12 , LiB 3 O 5 , and Li 2 O have been reported for Li–B oxide materials. The shortest distances between B and Li in these crystal systems were between 0.132 and 0.137 nm. Reverse Monte Carlo simulations of Li 2 O–2B 2 O 3 glass neutron diffraction showed that the first peak in the B–O PDF has two peak maxima at approximately 0.140 and 0.166 nm (values measured from an illustration in the paper) .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The first peaks are observed at 0.143 nm and ranged from 0.12 to 0.18 nm. Crystalline structures such as Li 2 B 4 O 7 , Li 3 B 7 O 12 , LiB 3 O 5 , and Li 2 O have been reported for Li–B oxide materials. The shortest distances between B and Li in these crystal systems were between 0.132 and 0.137 nm. Reverse Monte Carlo simulations of Li 2 O–2B 2 O 3 glass neutron diffraction showed that the first peak in the B–O PDF has two peak maxima at approximately 0.140 and 0.166 nm (values measured from an illustration in the paper) .…”
Section: Resultsmentioning
confidence: 93%
“…The Li structure in the LiBO 2 crystal systems was also studied using X-ray diffraction . The Li–O distances in the LiBO 2 crystals were 0.1945, 0.1960, 0.1970, 0.2007, and 0.2473 nm. , These local structures of Li–O pairs in the crystalline solids slightly varied in the melts. Two types of O are expected for the glass network form, where one is bridging oxygen atoms (O b ) bonding with two B and another is non-bridging oxygen atoms (O nb ) bonding with only one B within the coordination sphere.…”
Section: Resultsmentioning
confidence: 98%
“…Let us look at whether the reported anomalies [15][16][17][18][19][20][21][22][23][24][25][26][27] are related to structural changes, i.e. whether they really correspond to structural phase transitions.…”
Section: Discussionmentioning
confidence: 99%
“…Unusual behaviours of LTB at low temperatures have also been observed in x-ray diffraction studies [17,18]. A new phenomenon has been revealed in LTB, which consists in a phase transition into an incommensurate phase under the influence of thermal cycling [19,20]. Anisimova et al [21] attribute the observed memory effect exhibited by the elastic modulus of LTB to incommensurate modulation in the crystal.…”
Section: Introductionmentioning
confidence: 93%
“…The crystal structure of LTB has been determined by Krogh-Moe [5]. Its structure at room temperature is tetragonal with space group C 12 4v and point group 4mm with the polar axis along the crystallographic c-axis [6]. The unit cell dimensions are a = 9.477 Å and c = 10.286 Å [7].…”
Section: Introductionmentioning
confidence: 99%